Value of Expanded Resections in C.B.P. - Sanjinés, Aníbal (Cirugía del Uruguay, 1982)
Enlarged surgery is defined. Different functional reper cussion of enlarged lobectomy and pneumonectomy is emphasized. Patients must be strictly selected and this kind of surgery should be performed only if there is a reas onable certainty that it could be curative. The best results are obtained with, enlarged lobectomy to the chest wall and tracheobroncheal tree as well as pneumectomy including mediastinal sPread. Resection of aorta, esophagus and superior cava vein are contraindications for surgery.